Makna Peningkatan Pendapatan Bagi Pelaku Umkm Pengguna Qris Di Wilayah Kampus Tegalboto Jember - Tabina Susan Auliani R P; Ahmad Sauqi; Saiful Amin (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study aims to analyze the meaning of increased revenue for MSME operators using QRIS in the Tegalboto Campus area of Jember. It employs a qualitative approach using a phenomenological method, grounded in marketing management theory and the concept of digital payments. Data were collected through observation, in-depth interviews, and documentation involving purposively selected MSME operators, and subsequently analyzed using NVivo 12 through processes of data reduction, coding, data display, and conclusion drawing. The findings reveal that increased revenue is interpreted not merely as a rise in financial profit, but also as an increase in the customer base, greater transaction ease and speed, improved financial management efficiency, and heightened consumer trust in the business. Despite facing challenges such as internet connectivity issues, administrative fees, and transaction delays, the informants continue to use QRIS because the perceived benefits outweigh the obstacles. Thus, QRIS is viewed as a tool for digital transformation that supports operational efficiency, service quality improvements, and revenue growth for MSMEs in the Tegalboto Campus area of Jember.